2015
DOI: 10.4193/rhin14.074
|View full text |Cite
|
Sign up to set email alerts
|

Manifestation of eosinophilic granulomatosis with polyangiitis in head and neck

Abstract: The data of the largest monocentric study presented here confirms the hypothesis of a frequent ENT involvement in EGPA patients, in whom rhinological and otological manifestations are most common. Therefore, treatment should include long term follow-up and should be managed interdisciplinary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Asthma should always be assessed in patients with AR by asking patients about wheezing, shortness of breath and sleep disturbance plus, if needed, an objective measurement such as spirometry 80 and vice versa in patients with asthma owing to the frequent co-occurrence of these disorders. Patients should also undergo ear inspection as otitis media with effusion (also known as glue ear) may be a co-morbidity in children with rhinitis and in adults with severe forms of rhinosinusitis 81 . The general examination needs to also include skin examination for atopic dermatitis, and, in patients with obstructive rhinitis, assessment of thyroid function by checking for slow relaxation after the ankle jerk and for eye signs such as puffiness, redness and/or bulging, as hypothyroidism.…”
Section: Examinationmentioning
confidence: 99%
“…Asthma should always be assessed in patients with AR by asking patients about wheezing, shortness of breath and sleep disturbance plus, if needed, an objective measurement such as spirometry 80 and vice versa in patients with asthma owing to the frequent co-occurrence of these disorders. Patients should also undergo ear inspection as otitis media with effusion (also known as glue ear) may be a co-morbidity in children with rhinitis and in adults with severe forms of rhinosinusitis 81 . The general examination needs to also include skin examination for atopic dermatitis, and, in patients with obstructive rhinitis, assessment of thyroid function by checking for slow relaxation after the ankle jerk and for eye signs such as puffiness, redness and/or bulging, as hypothyroidism.…”
Section: Examinationmentioning
confidence: 99%
“…ANCA positive 31%-58% 26,37 MPO ANCA positive 25%-50% 26,47 ENT involvement 48%-96% 37,38 Rhinologic CRSwNP 42%-51% 37,38 Change in sense of smell 40% 47 Nasal crusting 8%-43% 47,48 Otologic OME/CHL 3%-12% 26 59 although the importance of abstinence from cocaine for a good outcome cannot be overstated.…”
Section: Prevalence Of Ent Features Of Eosinophilic Granulomatosis Wimentioning
confidence: 99%
“…As expected, based on the diagnostic criteria for EGPA, which includes obstructive airway disease and nasal polyps, 22 the most common manifestations for patients in the current study were asthma, chronic sinusitis, and allergic rhinitis, largely consistent with previous real-world studies. 6,7,9 Despite the frequency of manifestations, particularly the strong link to ear, nose, and throat manifestations, 23 the median DCI score for this study's population was 1.0 out of 6. Another previous administrative claims study reported the mean Quan-Charlson Comorbidity Index (CCI) score of 1.8 for patients in the EGPA cohort, which was higher than the 0.8 CCI value reported in the same study for patients in the asthma cohort.…”
Section: Discussionmentioning
confidence: 64%